Relationship of Compliance with Medication With hypertension - Rivai, Abdur; Budiono, Nugrahadi Dwi Pasca; Si’umiyati, Si’umiyati (Journal of Public Health Science Research (JPHSR), 2020)
Elderly or Elderly is a group that due to age, physiological function of the body decreases due to the aging process so that non-communicable diseases get older and more diseases will appear in the elderly, and due to degenerative impairment occurs the body so it is susceptible to infectious diseases . Based on Riskesdas (2013), the most common diseases in the elderly are non-communicable diseases or PTM, namely Hypertension of 45.9% at age 55-64 years and 63.8% at age 75 years above. The purpose of this study was to determine the relationship between regularity of taking drugs with hypertension. This type of research is correlation analytic research with observational observational and retrospective approaches. The study population is all elderly with hypertension in Karang Werda Sejahtera Kelurahan Bendul Merisi Surabaya, sample size 24, sampling with total sampling. Hypertension variable data collection is done by observing measurements and compliance variables using the MMAS-8 questionnaire or Morisky Medication Adherence Scale, spearmen correlation test data analysis with α = 0 , 05 . The results obtained 1) there is a relationship between adherence to take antihypertensive medication with Hypertension with ρ = 0.010, 2) there is a relationship between knowledge of taking antihypertensive medication with Hypertension with ρ = 0.012, 3) There is a relationship between motivation to take antihypertensive medication with Hypertension with ρ = 0.012. Maintaining medication compliance is important to reduce morbidity and mortality in the elderly .